A case of brucellosis mimicking Crimean-Congo hemorrhagic fever - Ozge Metin; Turkan A. Teke; Zeynep G. Gayretli Aydin; Ayse Kaman; Fatma N. Oz; Gulsum I. Bayhan; Gonul Tanir (Elsevier, 2015)
Summary: Brucellosis is a zoonotic disease caused by Brucella spp. that is transmitted to humans by the ingestion of unpasteurized milk and other dairy products from infected animals or through close contact with secretions. Crimean-Congo hemorrhagic fever (CCHF) is a tick-borne disease caused by a virus that is transmitted to humans by ixoid tick bites, contact with blood and tissue of infected animals or contact with infected humans. The symptoms of brucellosis are non-specific; it can mimic other diseases. In this paper, we present a case of brucellosis that was initially evaluated as CCHF. We emphasize that brucellosis should be considered in the differential diagnosis of CCHF, especially in endemic countries. Keywords: Brucellosis, Crimean-Congo hemorrhagic fever, Endemic